A study on routing metrics to improve the quality of service in MANET environment - Kumar C. Satya; Sambasiva Rao N.; Venkata Rami Reddy G. (MATEC Web of Conferences, 2024)
MANETs, infrastructure-free, multi-hop networks with an in height grade of complexity and dispersed nodes. Without a permanent and dedicated infrastructure, a node can communicate with other nodes directly or via intermediary nodes. Routing procedures play a crucial role in enhancing the overall presentation of a dynamic network environment like a MANET, which is referred to as Quality of Service (QoS). Simply put, a number of routing protocols may employ a composite routing measure to determine the best path(s) for data transfer. The development of routing protocols for MANETs will be affected by routing metrics. Therefore, we look at quality-of-service-based MANETs. In this overview, we will examine the classification scheme for ad hoc routing methods, and we will evaluate the similarities and differences between various routing protocols. As such, we will give priority to suggestions that will result in the highest possible network performance and energy competence. In this work, we provide a summary of our research and recommendations for future directions for the subject.